SIV Coreceptor Specificity in Natural and Non-Natural Host Infection: Implications for Cell Targeting and Differential Outcomes from Infection - Wetzel, Katherine S.; Elliott, Sarah T.C.; Collman, Ronald G. (Current HIV Research, 2018)
Pathogenic HIV-1 infection of humans and SIVmac infection of macaques are the result of zoonotic transfer of primate immunodeficiency viruses from their natural hosts into non-natural host species. Natural host infections do not result in pathogenesis despite high levels of virus replication, and evidence suggests that differences in anatomical location and specific subsets of CD4+ T cells infected may underlie distinct outcomes from infection. The coreceptor CCR5 has long been considered the sole pathway for SIV entry and the key determinant of CD4+ cell targeting, but it has also been known that natural hosts express exceedingly low levels of CCR5 despite maintaining high levels of virus replication. This review details emerging data indicating that in multiple natural host species, CCR5 is dispensable for SIV infection ex vivo and/or in vivo and, contrary to the established dogma, alternative coreceptors, particularly CXCR6, play a central role in infection and cell targeting. Infections of non-natural hosts, however, are characterized by CCR5-exclusive entry. These findings suggest that alternative coreceptor-mediated cell targeting in natural hosts, combined with low CCR5 expression, may direct the virus to distinct populations of cells that are dispensable for immune homeostasis, particularly extralymphoid and more differentiated CD4+ T cells. In contrast, CCR5-mediated entry in non-natural hosts results in targeting of CD4+ T cells that are located in lymphoid tissues, critical for immune homeostasis, or necessary for gut barrier integrity. Thus, fundamental differences in viral entry coreceptor use may be central determinants of infection outcome. These findings redefine the normal SIV/host relationship in natural host species, shed new light on key features linked to zoonotic immunodeficiency virus transfer, and highlight important questions regarding how and why this coreceptor bottleneck occurs and the coevolutionary equilibrium is lost following cross-species transfer that results in AIDS.
Keywords: entry coreceptor